Democracia, lucha contra la pobreza y políticas alternativas de 41 estabilización - Páez, Pedro Francisco (2000)
This paper presents a framework for the democratic debate in the evaluation and design of alternative stabilization policies, stressing the role of poverty in the macroeconomic desequilibria. In a multi-period game, in which it acts as Stackelberg leader, the government minimizes a quadratic loss function using stochastic dynamic control techniques. A system of simultaneous equations represents the private agents' aggregate best responses that result from the general equilibrium solutions to the different agents' optimization problems. On this foundations, an cstimated model fur Ecuador, with quarterly data for the period 1936-98, combined with optimal control tools allows for simulations of this game-theoretical set up. The application of the model suggests that Ecuadorian economic policy had problems of instrumental instability during the sample period, implying that the applied style of adjustment policies would be intrinsically no viable. Optimal control applications show that room exists for the design of more egalitarian stabilization schemes and that hort run efforts to fight poverty need not be extremely expensive as the false dichotomy Orthodoxy/Populism pretends.